1981
DOI: 10.1021/j150626a040
|View full text |Cite
|
Sign up to set email alerts
|

Deactivation mechanism of excited acridine and 9-substituted acridines in water

Abstract: The deactivation processes of excited acridine, deuterated acridine, and 9-substituted acridines (9-methyl, 9-propyl, 9-chloro, and %amino) have been investigated in alkaline and acidic water. The photoreaction does not occur with the irradiation of 365-nm light. In acidic water the fluorescence lifetime T depends only slightly on the temperature and the lowest triplet yield +sT is negligibly low for all of the acridines. In alkaline water T decreases and +ST increases with increasing temperature; the inters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
47
0

Year Published

1982
1982
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 0 publications
6
47
0
Order By: Relevance
“…Figure 8) on the acridinium chromophore (E T % 2.0 eV). [43,44] On closer inspection, we note that the transient absorption spectrum attributed to the CT state of 8 is somewhat similar to that expected for the T 1 -T n absorption of the acridinium chromophore. [45] This might make it difficult to discriminate between these species.…”
Section: Long-lived Charge Separation In a Compact Zinc Chlorin-c 60 supporting
confidence: 72%
See 1 more Smart Citation
“…Figure 8) on the acridinium chromophore (E T % 2.0 eV). [43,44] On closer inspection, we note that the transient absorption spectrum attributed to the CT state of 8 is somewhat similar to that expected for the T 1 -T n absorption of the acridinium chromophore. [45] This might make it difficult to discriminate between these species.…”
Section: Long-lived Charge Separation In a Compact Zinc Chlorin-c 60 supporting
confidence: 72%
“…Such interaction is, however, very evident in the fluorescence spectrum. Whereas the isolated acridinium ion is known to display a strong and structured green fluorescence (maximum around 495 nm), [43,47] this is fully quenched in 9 and substituted by a weak, broad, and structureless emission in the far-red region (maximum 675 nm in acetonitrile). This behavior has been observed before and, without doubt, can be attributed to CT fluorescence, that is, emissive back electron transfer from a 1 CT state populated by charge transfer from the naphthyl donor to the acridinium ion.…”
Section: Long-lived Charge Separation In a Compact Zinc Chlorin-c 60 mentioning
confidence: 99%
“…Triplet state formation [11][12][13], excited state reduction [14,15], and relaxation between excited ππ * and nπ * states [11,[16][17][18] were reported for different acridine derivatives. The triplet state formation in some of acridines takes place very efficiently, however, it has already been reported [10] that there is no evidence of triplet state population of DSA dyes.…”
Section: Resultsmentioning
confidence: 99%
“…These states were found to play a crucial role in the excited state relaxation of some acridine derivatives [11,[16][17][18]. In most cases, the nπ * state of acridines is slightly higher than the ππ * state, however, it was also suggested that positions of ππ * and nπ * states in aprotic solvents may be inverted [12,20,21].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation